Plutonium isotopes in surface air of Prague in 1986-2006 - Hölgye, Z (Journal of environmental radioactivity, 2008)
Monitoring of 239,240Pu in surface air of Prague started in 1986 in connection with the Chernobyl accident. Measurable activities of 10-28 microBq m(-3) were found from 29 April 1986 to 5 May 1986. In the most of the monitoring periods of 1987-1996, activities of 239,240Pu in air were not measurable. Positive values for 239,240Pu and 238Pu in air could be obtained after installation of an aerosol sampler with higher flow-rate in 1997. Activity concentrations of 239,240Pu and 238Pu in Prague air in the most of quarters of 1997-2006 were in the range 0.53-5.06 and <0.16-1.10 nBq m(-3), respectively. Seasonal fluctuations can be found in content of 239,240Pu in air. Activity ratios of 238Pu/239,240Pu in air are higher than those in top soil, so it can be supposed that 238Pu is coming to air of Prague also from other sources than resuspension of fallout from atmospheric nuclear tests.
Keywords: Seasons; černobylská havárie; Chernobyl Nuclear Accident; pohyb vzduchu; radioaktivní látky znečišťující vzduch; dějiny 21. století; Air Movements; Air Pollutants, Radioactive; Plutonium; roční období; Czech Republic; plutonium; History, 20th Century; dějiny 20. století; History, 21st Century; Česká republika